The evaluation of cardiovascular response to exercise in healthy Turkish children - Akdur, Hülyat; Sözen, Ahmet Bilge; Yiğit, Zerrin; Oztunç, Funda; Kudat, Hasan; Güven, Ozen (The Turkish Journal of Pediatrics, 2009)
The purpose of our study was to determine the normal cardiovascular responses of healthy Turkish children to exercise and to determine the reference values. Two hundred and eighty-four healthy children (115 girls, 169 boys) aged 5-14 were enrolled in the study. Exercise time (ET), workload that can be tolerated with exercise (MET value), change in heart rate (A HR), peak systolic and peak diastolic blood pressures (SBPmax and DBPmax), change in systolic blood pressure (delta SBP), and peak rate-pressure product (RPPmax) were positively correlated with age. There was no correlation between peak heart rate (HRmax) and age and there was also no significant increase in change in diastolic blood pressure (delta DBP) with increasing age. The means +/- SD values for ET, workload, HRmax, delta HR, SBPmax, DBPmax, delta SBP, deltaDBP, and RPPmax were 13.18 +/- 1.4 min, 8.56 +/- 0.93 MET, 171.46 +/- 1.91/min, 67.22 +/- 6.65/min, 125.16 +/- 13.36 mmHg, 73.32 +/- 4.06 mmHg, 24.3 +/- 5.96 mmHg, 7.2 +/- 6.9 mmHg, and 21504.7 +/- 2176.4, respectively. The values found in our study may be accepted as reference values of healthy Turkish children for exercise testing. The formula modified as (200-age) x 0.85 is thought to be more suitable to predict the target heart rate in children.